CRIMINAL LIABILITY OF CORPORATE SHAREHOLDERS - Rr. Dijan Widijowati; Halim Darmawan, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Corporations in the form of Limited Liability Companies in Indonesia are regulated in Limited Liability Company Law No. 40 of 2007 concerning Limited Liability Companies, this Law regulates the liability of corporations and/or shareholders who commit acts against the law, but the liability that can be asked of shareholders does not exceed existing shares. This study uses normative legal research methods. The data used are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. For data analysis, the qualitative jurisdictional analysis method was used. From this research, it can be found that law enforcement against shareholders who commit acts against the law can be upheld and the outcome is that the action against the law which was originally a civil action and then turned into a criminal act. By using the Piercing, the corporate veil doctrine, shareholders who commit acts against the law can be sentenced to criminal and all their assets to cover the financial losses of the state due to their actions. It is universally applied on the basis of fraudulent acts carried out to rake in personal profit and by implementing civil forfeiture or civil recovery, the proceeds of crimes committed by shareholders are likely to be returned.